Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1.
a)\(\frac{4}{9}x^2+\frac{4}{3}xy+y^2\)
b)\(9a^2+3ab+\frac{1}{4}a^2\)
2.
a)\(\left(5x+2b\right)^2\)
b)\(\left(x+1\right)^2\)
c)\(\left(3x+1\right)^2\)
d)\(\left[\left(2x+3y\right)+1\right]^2\)
1,
\(\left(\frac{2}{3}x+y\right)^2=\left(\frac{2}{3}x\right)^2+2.\frac{2}{3}x.y+\left(y\right)^2=\frac{4}{9}x^2+\frac{4}{3}xy+y^2\)
\(\left(3a+\frac{1}{2}b\right)^2=\left(3a\right)^2+2.3a.\frac{1}{2}b+\left(\frac{1}{2}b\right)^2=9a^2+3ab+\frac{1}{4}b^2\)
2,
\(25a^2+4b^2+20ab=\left(5a\right)^2+\left(2b\right)^2+2.5a.2b=\left(5a+2b\right)^2\)
\(x^2+2x+1=\left(x\right)^2+2.x.1+\left(1\right)^2=\left(x+1\right)^2\)
\(9x^2+6x+1=\left(3x\right)^2+2.3x.1+\left(1\right)^2=\left(3x+1\right)^2\)
\(\left(2x+3y\right)^2+2.\left(2x+3y\right)+1=\left(2x+3y+1\right)^2\)
1, a^2 - 4b^2
= a^2 - (2b)^2
=(a-2b)(a+2b)
2, 1/4 a^2 - b^2
=(1/2a)^2 -b^2
=(1/2a-b)(1/2a+b)
3, (a-2b)^2 - (3a+b)^2
= (a-2b-3a-b)(a-2b+3a+b)
= (-2a-3b)(4a-b)
a, x2-7x-14y+2x
=x(x+2)-7(x-2y)
b, x3-4x2y+4xy2-25x
=x3-4x2y+4xy2-y3-25x+y3
=(x-y)3-25x+y3
a ) = x(x+2) - 7(x+2y)
b) = -4 xy ( x-y) + (x^3-25x) [ câu này mk , chaqcs là làm đúng đâu ]
\(2-25x^2=0\Leftrightarrow25x^2=2\Leftrightarrow x^2=\frac{2}{25}\Leftrightarrow x=\frac{\sqrt{2}}{5}\)
ta có :\(2-25x^2=0\)
\(\sqrt{2}^2-\left(5x\right)^2=0\)
\(\left(\sqrt{2}-5x\right)\left(\sqrt{2}+5x\right)=0\)
suy ra \(\orbr{\begin{cases}\sqrt{2}-5x=0\\\sqrt{2}+5x=0\end{cases}}\)tương đương \(\orbr{\begin{cases}5x=\sqrt{2}\\5x=-\sqrt{2}\end{cases}}\)tương đương \(\orbr{\begin{cases}x=\frac{\sqrt{2}}{5}\\x=-\frac{\sqrt{2}}{5}\end{cases}}\)
Vậy \(x=\frac{\sqrt{2}}{5}\)hoặc \(x=-\frac{\sqrt{2}}{5}\)
\(25a^2+4b^2-20ab=\left(5a\right)^2-2.5a.2b+\left(2b\right)^2=\left(5a-2b\right)^2.\)
\(2-25x^2=0\)
\(\Rightarrow25x^2=2\)
\(\Rightarrow x^2=\frac{2}{25}\)
\(\Rightarrow x=\frac{\sqrt{2}}{5}\)
tíc mình nha
\(2-25x^2=0\)
\(\Leftrightarrow\left(\sqrt{2}-5x\right)\left(\sqrt{2}+5x\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}\sqrt{2}-5x=0\\\sqrt{2}+5x=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{\sqrt{2}}{5}\\x=-\frac{\sqrt{2}}{5}\end{cases}}\)
Vậy: \(x=\orbr{\begin{cases}x=\frac{\sqrt{2}}{5}\\x=-\frac{\sqrt{2}}{5}\end{cases}}\)
b) \(x^2-x+\frac{1}{4}=0\)
\(\Leftrightarrow\left(x-\frac{1}{2}\right)^2=0\)
\(\Leftrightarrow x-\frac{1}{2}=0\)
\(\Leftrightarrow x=\frac{1}{2}\)
*\(x^2-x+\frac{1}{4}=x^2-2.x.\frac{1}{2}+\left(\frac{1}{2}\right)^2=\left(x-\frac{1}{2}\right)^2\)
*\(25a^2+4b^2-20ab=\left(5a\right)^2-2.5a.2b+\left(2b\right)^2=\left(5a-2b\right)^2\)
*\(9x^2+y^2+6xy=\left(3x\right)^2+2.3x.y+y^2=\left(3x+y\right)^2\)
\(25a^2\) chứ :)?
\(25x^2\) hay \(25a^2\) ?